Volcanism straddling the Miocene–Pliocene boundary on Patmos and Chiliomodi islands (southeastern Aegean Sea): insights from new 40Ar ∕ 39Ar ages - K. M. Boehm; K. F. Kuiper; B. Uzel; P. Z. Vroon; J. R. Wijbrans (Geochronology, 2023)
The island of Patmos, in the eastern Aegean Sea, consists almost entirely of late Miocene to Pliocene volcanic rocks. The magmatism in the Aegean is governed by subduction of the African plate below the Eurasian plate, back-arc extension, slab rollback, slab edge processes and westward extrusion of central Anatolia to the west along the Northern Anatolian Fault into the Aegean domain. The evolution of the Aegean basin is that of a back-arc setting, with a southerly trend in the locus of both convergent tectonics and back-arc stretching, allowing intermittent upwelling of arc, lithospheric and asthenospheric magmas.